056 Perampanel and secondarily generalised seizures in a pooled analysis of phase III studies and their open-label extension: effect of enzyme-inducing antiepileptic drugs. Issue 6 (24th May 2018) - Ko, David; Williams, Betsy; Patten, Anna; Laurenza, Antonio
Abstract : Introduction: Perampanel is approved for adjunctive treatment of partial seizures, with or without secondarily generalised seizures (SGS), and primary generalised tonic-clonic seizures in epilepsy patients aged ≥12 years. Approval of perampanel for partial seizures was based on three randomised, double-blind, placebo-controlled, Phase III Studies 304 (NCT00699972 ), 305 (NCT00699582 ) and 306 (NCT00700310 ); patients completing these could enter open-label extension (OLEx) Study 307 (NCT00735397 ). Here, we report efficacy of perampanel as adjunctive treatment of SGS by co-administration of enzyme-inducing antiepileptic drugs (EIAEDs) versus non-EIAEDs in both the Phase III and OLEx studies. Methods: In the double-blind studies, patients (≥12 years) with partial seizures, with or without SGS, receiving 1–3 AEDs at Baseline were randomised to placebo or 2–12 mg/day perampanel for 19 weeks. In the OLEx, patients received ≤12 mg/day perampanel for ≤272 weeks. Efficacy assessments included median percent change in SGS frequency/28 days, SGS 50% and 75% responder and seizure-freedom rates. Results: For patients with SGS at pre-perampanel Baseline, 564 were in the double-blind studies and 388 received perampanel for ≥1 year in the OLEx. In the double-blind studies, perampanel co-administered with an EIAED (carbamazepine, eslicarbazepine, oxcarbazepine, phenytoin) had reduced efficacy compared with non-EIAEDs due to increased clearance; this was particularly evident at higher doses, although these differences were still greater than placebo. In the OLEx, concomitant administration of both non-EIAEDs and EIAEDs was associated with sustained efficacy, with slightly better efficacy during the first, second and third years of perampanel exposure for non-EIAEDs compared with EIAEDs. Conclusion: Perampanel demonstrated good and sustained long-term efficacy against SGS. With the recent FDA approval of perampanel for monotherapy use for partial seizures, non-EIAED data may be more relevant for consideration if perampanel is used as a single agent (no other AED) while real-world data and experience are accumulated. Study support: Eisai Inc.